Evidence that Orai1 does not contribute to store-operated TRPC1 channels in vascular smooth muscle cells - Shi, Jian (2017)
Fil: Shi, Jian. University of Leeds. School of Medicine. Institute of Cardiovascular & Metabolic Medicine; Reino Unido